Effects of Genetic Variation on Endurance Performance, Muscle Strength, and Injury Susceptibility in Sports: A Systematic Review - Appel, Milena; Zentgraf, Karen; Krüger, Karsten; Alack, Katharina (Frontiers in Physiology, 2021)
The aim of this systematic review was to assess the effects of genetic variations and polymorphisms on endurance performance, muscle strength and injury susceptibility in competitive sports. The electronic databases PubMed and Web of Science were searched for eligible studies. The study quality was assessed using the RoBANS tool. Studies were included if they met the following criteria: (1) human study in English or German; (2) published in the period 2015 to 2019; (3) investigation of an association between genetic variants and endurance performance and/or muscle strength and/or endurance/strength training status as well as ligament, tendon, or muscle injuries; (4) participants aged 18 to 60 years and national or international competition participation; (5) comparison with a control group. 19 studies and one replication study were identified. Results revealed that the IGF-1R 275124 A>C rs1464430 polymorphism was overrepresented in endurance trained athletes. Further, genotypes of PPARGC1A polymorphism correlated with performance in endurance exercise capacity tests in athletes. Moreover, the RR genotype of ACTN3 R577X polymorphism, the C allele of IGF-1R polymorphism and the gene variant FTO T>A rs9939609 and/or their AA genotype were linked to muscle strength. In addition, gene variants of MCT1 (T1470A rs1049434) and ACVR1B (rs2854464) were also positively associated with strength athletes. Among others, the gene variants of the MMP group (rs591058 and rs679620) as well as the polymorphism COL5A1 rs13946 were associated with susceptibility to injuries of competitive athletes. Based on the identified gene variants, individualized training programs for injury prevention and optimization of athletic performance could be created for competitive athletes using gene profiling techniques.